The Influence of Self Cofidence in Public Speaking - Eni, Nur; Warastri, Nasywa Tsany; Mutiani, Mutiani; Ilhami, M. Ridha; Sari, Raihanah (Journal of Social Development, 2024)
This journal article discusses the influence of self-confidence on public speaking skills in adolescents. This article finds interesting facts that social interaction with the environment and even includes support from peers, family, and teachers, plays an important role of one's self in shaping and increasing one's self-confidence. From the results of the interviews and questionnaires that we distributed, it can be concluded that for someone to improve their public speaking skills, efforts are also needed to strengthen and increase their confidence through positive social interaction and also support from the surrounding environment. From this article, it is hoped that it can contribute even to the development of educational strategies as well as effective interventions to improve public speaking skills in everyone. The research methods used include interviews and questionnaire distribution. The questionnaire was distributed to collect quantitative data on the level of confidence and its influence on public speaking skills. The results of our study show that self-confidence has a significant role in determining a person's success in public speaking. A person with a high level of confidence tends to be better able to overcome fear and anxiety, and is more effective in conveying their message to the audience. The hope of the discussion in this article is that we can all learn and even understand that there are causes and effects experienced by others that are certainly different from what we experience. So that we can also learn to see someone's reasoning from another point of view.